Analisis Yuridis tentang Perlindungan Konsumen pada E-Commerce di Indonesia: Pendekatan Yuridis-Normatif - Yulianingsih, Sri; Putra, Rengga Kusuma (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
This study focuses on the juridical analysis of consumer protection in e-commerce transactions in Indonesia, considering the sector's rapid growth, which reached a total transaction value of IDR 631 trillion in 2023. On the other hand, consumer complaints have continued to rise, involving issues such as fraud, defective products, and data privacy violations. This study aims to evaluate the effectiveness of existing regulations, such as Law No. 8 of 1999 and its supporting regulations, in protecting consumer rights. Using a normative-juridical approach, the study examines the legal substance, implementation, and gaps between national regulations and international standards like the European Union's General Data Protection Regulation (GDPR). The findings indicate that although national regulations provide basic protections, their effectiveness is considered low, particularly in the aspect of personal data protection, which only achieves 40% effectiveness, significantly lagging the GDPR at 95%. Additionally, inefficient complaint mechanisms and weak coordination among government agencies are major obstacles to resolving consumer disputes. Low digital literacy among consumers further exacerbates the ineffectiveness of the protection provided by existing regulations. The study concludes that national regulations require significant reform to be more adaptive to digital challenges. Policy recommendations include adopting GDPR principles, strengthening government oversight, and enhancing consumer education. This study's contribution is expected to strengthen a safe, transparent, and equitable e-commerce ecosystem in Indonesia while boosting consumer trust in online transactions.